2019
DOI: 10.3171/2017.12.jns171545
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cochlear nerve mapping with the mobile cochlear nerve compound action potential tracer in vestibular schwannoma surgery

Abstract: OBJECTIVE The authors describe the usefulness and limitations of the cochlear nerve compound action potential (CNAP) mobile tracer (MCT) that they developed to aid in cochlear nerve mapping during vestibular schwannoma surgery (VSS) for hearing preservation. METHODS This MCT device requires no more than 2 seconds for stable placement on the nerve to obtain the CNAP and thus is able to trace the cochlear nerve instantaneously. Simultaneous bipolar and monopolar recording is possible. The authors present the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…In recent years, numerous studies have reported a significant decrease in the number of large VSs (Koos grade IV). The recent reported incidence is between 2% and 12.5% [ 10 , 16 , 28 ]. This is most likely due to an increase in early diagnoses [ 2 , 4 , 19 , 32 , 33 , 34 , 35 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, numerous studies have reported a significant decrease in the number of large VSs (Koos grade IV). The recent reported incidence is between 2% and 12.5% [ 10 , 16 , 28 ]. This is most likely due to an increase in early diagnoses [ 2 , 4 , 19 , 32 , 33 , 34 , 35 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…The patients in our study were a retrospective sample who underwent operations on Koos grade IV VSs between January 2007 and December 2015 in the Department of Neurosurgery, Emergency County Hospital, Târgu Mureş, Romania. To quantify risk and predict the surgical outcome, we chose the Koos grading system, as previous research has proven its validity [ 4 , 26 , 27 , 28 ].…”
Section: ⧉ Patients Matherials and Methodsmentioning
confidence: 99%
“…Recently, intraoperative adjunctive with cochlear mapping with the mobile cochlear nerve compound action potential tracer in VS surgery has been also suggested 20 . While this device might be useful in cochlear nerve mapping and consequently help in hearing preservation, it has also several limitations.…”
Section: Dear Editormentioning
confidence: 99%
“…Although new developments based on thin metal wires have been attempted 18,19 , none of the existing probes can maintain stable and reliable recording during routine neurosurgical manipulations, as they inevitably are subjected to tugging, displacing, and bending motions. To address the limitations of current CINM devices 14,18,19,22 , we developed a biomechanically compatible, suture-free, and individually reconfigurable CINM based on soft and stretchable organic bioelectronic devices (Fig. S1).…”
Section: Introductionmentioning
confidence: 99%
“…However, these far-field signals are typically weak, requiring long-time acquisition and summation to achieve discernable signal-to-noise ratios. As a result, far-field potential recording itself is insufficient to provide high-quality physiological monitoring in real time [14][15][16] . In addition, many tumor-bearing patients already have considerable pre-operative neurological symptoms, which further lower the source neural signals.…”
Section: Introductionmentioning
confidence: 99%